2014
DOI: 10.1248/bpb.b14-00058
|View full text |Cite
|
Sign up to set email alerts
|

Novel siRNA Delivery System Using a Ternary Polymer Complex with Strong Silencing Effect and No Cytotoxicity

Abstract: We developed a novel small interfering RNA (siRNA) delivery system using a ternary complex with polyethyleneimine (PEI) and γ-polyglutamic acid (γ-PGA), which showed silencing effect and no cytotoxicity. The binary complexes of siRNA with PEI were approximately 73-102 nm in particle size and 45-52 mV in ζ-potential. The silencing effect of siRNA/PEI complexes increased with an increase of PEI, and siRNA/PEI complexes with a charge ratio greater than 16 showed significant luciferase knockdown in a mouse colon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, a ternary complex of pDNA/protamine/γPGA ( Figure 5A) was taken up by clathrinmediated endocytosis and macropinosytosis and showed high transfection ef iciency in B16-F10 cells [75]. In addition, a ternary complex of siRNA/PEI/γPGA ( Figure 5A) showed a high gene silencing effect and no cytotoxicity in B16-F10 cells [76]. From these indings, ternary complexes with γPGA may be a potential carrier for targeting tumor cells.…”
Section: Nucleic Acidmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, a ternary complex of pDNA/protamine/γPGA ( Figure 5A) was taken up by clathrinmediated endocytosis and macropinosytosis and showed high transfection ef iciency in B16-F10 cells [75]. In addition, a ternary complex of siRNA/PEI/γPGA ( Figure 5A) showed a high gene silencing effect and no cytotoxicity in B16-F10 cells [76]. From these indings, ternary complexes with γPGA may be a potential carrier for targeting tumor cells.…”
Section: Nucleic Acidmentioning
confidence: 90%
“…Anionic polymer or its conjugate Cationic polymer or liposome Reference pDNA ᵞPGA Chitosan [66,67] pDNA ᵞPGA Dendrigraft poly-L-lysine [80] pDNA ᵞPGA PEI [81][82][83] pDNA ᵞPGA Protamine [75] pDNA αPGA DOTAP/Chol liposome [54] siRNA ᵞPGA Chitosan [73] siRNA ᵞPGA Dendrigraft poly-L-lysine [74] siRNA αPGA DOTAP/Chol liposome [77] siRNA αPGA DMAPAP/DOPE liposome [78,79] siRNA ᵞPGA PEI [76] pDNA Heparin Cationic glycopolymer (Tr4) [84] pDNA Heparin-PEI - [85] pDNA Alginic acid, Pectin Lipofectamine 2000 [24] pDNA: plasmid DNA, siRNA: small interfering RNA, ᵞPGA: poly-ᵞ-glutamic acid, αPGA: poly-α-glutamic acid, PEI: polyethylenimine, DMAPAP: 2-{3-[bis-(3-amino-propyl)-amino]-propylamino}-N-ditetradecyl carbamoyl methylacetamide, Chol: cholesterol, DOPE: 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine.…”
Section: Nucleic Acidmentioning
confidence: 99%
“…In this study, a high amount of PEI was used to prepare nanoparticles which showed high transfection efficiency ( Figure 3 B,C) but also exhibited severe cytotoxicity ( Figure 4 A,B). One promising approach to reduce the cytotoxicity is to incorporate or recharge anionic polymers into the cationic PEI complexes [ 26 , 29 , 30 , 53 ]. Therefore, in this study, γ-PGA was incorporated into γ-DDNPs and resulted in the high gene/siRNA transfection efficiency with minor cytotoxicity ( Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, during modifications, care should be elicited not to induce any changes in the siRNA specificity or their silencing activity. A novel siRNA delivery system was created with ternary complex of polyethyleneimine (PEI) and c-polyglutamic acid [14]. This complex displayed a prominent silencing activity almost equal to the lipofectamine complex with siRNA and no cytotoxicity being reported.…”
Section: Sirna Delivery Complications and Interventionsmentioning
confidence: 99%